(untitled) - Couchman, Jason S. (Berkeley, Calif., 1998)
Certification books are selling very well--and even small market topics are supporting books. With Oracle's release of the first OCP Database Administrator Track exam, candidates will be looking for a solid guide in preparing for the exam. Though only an estimated 3-5,000 will take the test this year, it's expected that three or four times that amound will buy the book to obtain the valuable information. Inclusion of additional exam coverage for OCP Oracle8 Certified DBA candicates will braoden the market and lengthen the book's shelf life.
Keywords: Oracle (tệp máy tính),Oracle (Computer file)